2021
DOI: 10.3389/fmed.2021.810651
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prior to Intensive Care Unit Statin Use With Outcomes on Patients With Acute Kidney Injury

Abstract: Purpose: To evaluate the association of prior to intensive care unit (ICU) statin use with the clinical outcomes in critically ill patients with acute kidney injury (AKI).Materials and Methods: Patients with AKI were selected from the Medical Information Mart for Intensive Care IV (version 1.0) database for this retrospective observational study. The primary outcome was 30-day intensive care unit (ICU) mortality. A 30-day in-hospital mortality and ICU length of stay (LOS) were considered as secondary outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…A retrospective cohort study demonstrated that the risk of early mortality after primary coronary artery bypass graft surgery was reduced by preoperative statin therapy ( Pan et al, 2004 ). Although there was some research on whether pre-ICU statin use can improve the mortality of patients with AKI ( Tu et al, 2021 ) and sepsis ( Chinaeke et al, 2021 ) in the MIMIC database, there is no research on CSA-AKI patients. We mainly studied whether using statins in the pre-ICU is related to the clinical outcome of patients with CSA-AKI and whether it can reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A retrospective cohort study demonstrated that the risk of early mortality after primary coronary artery bypass graft surgery was reduced by preoperative statin therapy ( Pan et al, 2004 ). Although there was some research on whether pre-ICU statin use can improve the mortality of patients with AKI ( Tu et al, 2021 ) and sepsis ( Chinaeke et al, 2021 ) in the MIMIC database, there is no research on CSA-AKI patients. We mainly studied whether using statins in the pre-ICU is related to the clinical outcome of patients with CSA-AKI and whether it can reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who met the following criteria were included in the study: 1) first ICU and first hospital admission; 2) hospital stay >48 h; and 3) patients undergoing cardiac surgery during hospitalization and diagnosed with AKI within 1 week after surgery. We excluded patients with preoperative AKI, ESKD, with statins use after admission but without statins before admission ( Tu et al, 2021 ), and aged <18 years. Finally, 675 pre-ICU statin users and 2095 non-users were enrolled in this study ( Figure 1 ), divided into groups pre-ICU statin use and non-use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations